Argumentasi Biblikal Terhadap Pernikahan Sesama Jenis - Siregar, Jonri Muksen; Silaban, Guntur H.S. (JURNAL LUXNOS, 2025)
The issue of same-sex marriage has become one of the most complex debates within contemporary social, legal, and Christian theological contexts. Within Christian theology, the primary challenge lies in divergent interpretations of biblical texts: whether Scripture normatively rejects same-sex relationships or whether these texts should be reinterpreted contextually in light of modern social developments. This study aims to explore the theological meanings embedded in biblical texts related to the issue of same-sex marriage. The scope of the study includes biblical interpretation, contextual and pastoral responses of the church, as well as linguistic analysis of key terms in the Hebrew and Greek languages. The research employs a qualitative approach through library research, utilizing hermeneutics as the primary method of textual analysis based on historical, cultural, and linguistic contexts. The theoretical framework is grounded in biblical foundations, particularly the creation narrative of male and female and the biblical concept of marriage. The findings indicate that the Bible consistently does not support the concept of same-sex marriage, as affirmed in passages such as Leviticus 18:22 and Romans 1:26–27. Homosexual practices are categorized as forms of moral and spiritual deviation resulting from the rejection of divine will. Nevertheless, the biblical message also offers a path of restoration through grace in Christ.